ʺGamification in engineering specialists trainingʺ - Ovcharenko, O.; Tupchenko, V. (Problems of Engineer-Pedagogical Education, 2022)
Problems of improving the quality of higher education for engineering specialists through introduction of a gamified learning space are considered in the article. Modern experience of using gamification in business with a possibility of transferring it to the education system is discussed. In particular, the reform of higher education carries elements of gamification. Main elements of gamified education systems such as mechanics, scenario, aesthetics, and technologies are determined. Mechanics that can be used for gamification are analyzed. Examples of providing the functionality of studying engineering disciplines with the help of mechanics are given. The system of accumulating points during training is already actively used by teachers; an element of randomness and nonlinearity in the accrual of points can make it more effective. Fundamentally new mechanics for education space are the use of rewards and introduction of game currency. Together they open the way for introduction of accumulation and trade in resources. The rating should be used very carefully as it can negatively affect the involvement of higher education students in the trading process. Each result is important and needs to be constantly emphasized. Principles of increasing motivation in gamified systems, possibility of providing a unique education trajectory for a student, as well as acquiring such general competencies as the ability to work independently and in a team, have been investigated. Influence of a plot on learners’ desire to continue studying is considered. Variants of subject lines development of engineering specialties professional disciplines are proposed. Influence of the aesthetic component and technologies on efficiency of the gamified system is analyzed. Examples of using technologies of the modular object-oriented dynamic learning environment Moodle are given and they are compared with a full-fledged software shell. The article states that despite the fundamentally new form of the motivation system in the gamified course its main task is to achieve programmed learning outcomes by students.